Marketing by live streaming: How to interact with consumers to increase their purchase intentions - Liu, Feng; Wang, Yan; Dong, Xiaoxu; Zhao, Huawei (Frontiers in Psychology, 2022)
Live streaming e-commerce, as a kind of new information technology-based business model, is currently the most popular marketing approach, especially in China. This research divides live streaming interactions into three dimensions, interactions for obtaining product information (IPI), interactions for grasping the purchase dynamics of others (IPD), and interactions for obtaining monetary incentives (IMI), and proposes a comprehensive framework to examine whether live streaming interactions with consumers promote both social presence and consumer conformity, and thereby enhance their purchase intentions. Covariance-based structural equation modeling (CB-SEM) with AMOS was conducted to analyze data collected from 576 Chinese consumers. The main findings are that, first, both IPI and IPD can exert a direct impact on social presence and consumer conformity; second, IMI has a positive impact only on social presence; third, among the three dimensions of interactions, both IPI and IPD tend to increase purchase intention through social presence and consumer conformity, while IMI increases purchase intention only via social presence. Furthermore, given the differences between experience and search products, the results of the multigroup analysis indicate inconsistent path coefficients between the two product groups. This study provides a novel perspective on live streaming e-commerce with evidence on how interactions matter in driving purchase intentions, enriches the content of live streaming e-commerce literature and explores the practical implications for marketing managers are looking for marketing by live streaming.